Emerging trends and research foci of epithelial–mesenchymal transition in gliomas: A scientometric analysis and review - Xing, Yang; He, Minghua; Su, Zhenjin; Yasinjan, Feroza; Liu, Jiankai; Wang, Hong; Cui, Jiayue; Hong, Xinyu (Frontiers in Oncology, 2022)
Background: Epithelial-mesenchymal transition (EMT) is a key factor in the invasion and migration of glioma cells, and the study on EMT in gliomas has been becoming a hot topic over the past decade. The scientometric analysis is getting more attention since it can obtain hot topics and emerging trends in a research field. And this article analyzed the research related to EMT in gliomas for the first time, including descriptions of research situations, evaluations of research foci, and predictions of emerging trends. Methods: We searched the topic-related original articles from January 2012 to December 2021 in the Web of Science Core Collection (WoSCC) by using a specific strategy and a total of 1217 publications were obtained. The WoS platform, VOS viewer, and Citespace were used to analyze the annual distribution of publications and citations, authors and density of keywords, and other analyses including countries, institutions, references, and clustering, burst analysis and the timeline view of keywords, correspondingly. Results: The scientometric analysis identified that the study of EMT in gliomas developed fast and received continuous attention in the last decade. Based on the results of data analysis, most publications on the topic were coming from China, and the USA had the highest betweenness centrality. The top 10 co-cited references revealed the landmark documents which had greatly promoted the development of this field. The major focus is on the cellular and molecular mechanisms of EMT in gliomas, and the therapy related to EMT target and noncoding RNAs have been developing fast in recent years. Conclusions: This study revealed the intimate connections between EMT and gliomas, and the complex mechanisms regulating EMT in gliomas had been studied widely in the last decade. Exploring the deep mechanisms of EMT in gliomas is the foundation of the targeted inhibitions, which can promote the development of therapies for gliomas.